Chemical conversion solution, chemical conversion treatment method for aluminum substrate, chemically treated substrate, electrode material for aluminum electrolytic capacitor, and capacitor
A chemical conversion solution with smectite and water improves both capacitance and voltage resistance of aluminum substrates, addressing the trade-off in existing methods and enhancing performance for electrolytic capacitors.
Patent Information
- Application Number
- JP2021150037
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-15
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2041-09-15
AI Technical Summary
Existing chemical conversion methods for aluminum substrates in capacitors face a trade-off between high capacitance and withstand voltage, where increasing one typically decreases the other.
A chemical conversion solution containing smectite and water is used to anodize aluminum substrates, forming an oxide film that enhances both electrostatic capacity and voltage resistance.
The treated substrate achieves a significant increase in capacitance while maintaining high voltage resistance, making it suitable for aluminum electrolytic capacitors.
Smart Images

Figure 0007660843000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a chemical conversion liquid, a chemical conversion treatment method for an aluminum-containing substrate using the chemical conversion liquid, a chemically treated substrate obtained by the chemical conversion treatment method, an electrode material for an aluminum electrolytic capacitor including the chemically treated substrate, and a capacitor including the electrode material for an aluminum electrolytic capacitor. [Background technology]
[0002] Aluminum substrates are used for electrodes for capacitors and wiring for various electronically conductive circuits. When used as a capacitor, it is necessary to form an oxide film on the aluminum surface that acts as a dielectric. For example, a chemical conversion method using anodization is known as a method for forming such a film. This method is a method in which an oxide film is formed on the surface of a substrate such as aluminum or an aluminum alloy by electrochemically oxidizing the surface of the substrate in a chemical conversion solution. In this case, the higher the capacitance and withstand voltage of the oxide film, the more useful the device will be in industry. However, for the same electrode area, there is a problem in that the capacitance decreases when the withstand voltage is increased.
[0003] As a method for forming an oxide film with high electrostatic capacity on an aluminum substrate by chemical conversion treatment, a method of performing chemical conversion treatment using a chemical conversion solution containing boric acid, ammonium borate, branched polypropylene glycol, and water has been disclosed (Patent Document 1). Also, as a method for suppressing electrolytic corrosion on an aluminum alloy during chemical conversion treatment and thereby forming a good oxide film, a surface conditioner with a pH of 3 to 12 that contains zinc phosphate particles with a D50 of 3 μm or less, a water-soluble organic polymer, and a layered clay mineral and is used before the phosphating of metals, and further contains a divalent or trivalent metal nitrite compound, zinc oxide and / or sodium hydroxide, and a nonionic or anionic surfactant as a function-imparting agent has been disclosed (Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-102595 A [Patent Document 2] International Publication No. 2007 / 013626 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention aims to provide a chemical conversion liquid capable of producing a chemically treated substrate that is suitable as an electrode material for an aluminum electrolytic capacitor and that has both a high electrostatic charge and a high withstand voltage. The present invention also aims to provide a method for chemically treating an aluminum substrate using the chemical conversion liquid, and a chemically treated substrate obtained by the chemical conversion method. A further object of the present invention is to provide an electrode material for an aluminum electrolytic capacitor that includes the chemically treated substrate, and a capacitor that includes the electrode material for an aluminum electrolytic capacitor. [Means for solving the problem]
[0006] As a result of extensive research, the inventors discovered that a chemical conversion-treated substrate having large capacitance and maintained voltage resistance, which is suitable as an electrode material for aluminum electrolytic capacitors, can be obtained by using a chemical conversion solution containing smectite, a type of clay mineral, and thus arrived at the present invention.
[0007] That is, the above-mentioned object of the present invention is achieved by the following means: [1] at least, (A) Smectite (B)Water A chemical conversion solution containing: [2] The chemical conversion solution according to [1], wherein the smectite is synthetic smectite. [3] The chemical conversion liquid according to [1] or [2], wherein the content of smectite in the chemical conversion liquid is 0.1 to 20 mass %. [4] A method for chemically treating an aluminum base material, the method comprising the steps of: anodizing an aluminum base material with the chemical conversion solution according to any one of [1] to [3] to obtain a chemically treated base material having an aluminum oxide film formed on its surface. [5] A chemically treated substrate obtained by the chemical conversion treatment method according to [4]. [6] An electrode material for an aluminum electrolytic capacitor, comprising the chemically converted substrate according to [5]. [7] A capacitor comprising the electrode material for an aluminum electrolytic capacitor according to [6].
[0008] According to the chemical conversion liquid of the present invention and the method for chemically treating an aluminum substrate using the chemical conversion liquid, a chemically treated aluminum substrate having a large electrostatic capacity and excellent voltage resistance can be obtained. The chemically treated substrate of the present invention has a high electrostatic capacity and a high voltage resistance, and is suitable as an electrode material for an aluminum electrolytic capacitor, and the electrode material for an aluminum electrolytic capacitor is suitable as a capacitor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, preferred embodiments of the present invention will be described in detail, but the present invention is not limited to these embodiments except as specified in the present invention.
[0010] The chemical conversion liquid according to one embodiment of the present invention is used, for example, to perform a chemical conversion treatment on an aluminum substrate by anodization, thereby producing a chemically-treated substrate having an aluminum oxide film formed on its surface.
[0011] By using the chemical conversion solution of this embodiment, a wide variety of metal substrates can be anodized. Examples of metals constituting the substrate to be anodized include aluminum and aluminum alloys, which can be made into a capacitor by an oxide coating. There are no particular limitations on the type of metal to be combined with aluminum to form the aluminum alloy. By using the chemical conversion solution of this embodiment, substrates made of aluminum and aluminum alloys that can be used as electrode materials for aluminum electrolytic capacitors can be effectively anodized.
[0012] (Aluminum base) The material of the "aluminum substrate" (hereinafter also simply referred to as "substrate") in this specification is not particularly limited as long as it is a metal mainly composed of aluminum. A suitable substrate material is, for example, pure aluminum (aluminum with a purity of 99% or more) in the case of aluminum alone, more preferably with a purity of 99.9% or more, and most preferably with a purity of 99.99% or more. Aluminum alloys containing aluminum as the main component can also be used. In the case of an aluminum capacitor, the substrate may have a shape such as a foil, plate, metal wire, or a molded body using these. The thickness of the aluminum oxide film formed on the surface of the chemically treated substrate is not particularly limited, but is preferably in the range of 1 nm to 2 μm.
[0013] (chemical liquid) The chemical conversion solution in this embodiment is a composition containing smectite and water as essential components. The smectite component is presumed to be a component that increases the capacitance while maintaining the withstand voltage of the oxide film formed by chemical conversion. In addition, water is a solvent component. For example, by electrochemically anodizing an aluminum substrate using the chemical conversion solution of this embodiment, an aluminum oxide film, which is an oxide film, is formed on the substrate surface, and a chemically treated substrate with large capacitance that is suitable as an electrode material for aluminum electrolytic capacitors can be produced.
[0014] (Smectite) The type of smectite contained in the chemical conversion solution in this embodiment is not particularly limited and can be appropriately set depending on the purpose. Smectite can be natural or synthetic, but since it is preferable to use a material that contains as few impurities as possible, synthetic smectite is particularly preferable. The smectite is preferably one or more selected from montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, and stevensite, and more preferably one or more selected from hectorite, saponite, and stevensite.
[0015] The interlayer cationic species of the smectite used in the present invention is not particularly limited. However, it is particularly preferred that the smectite contains sodium or lithium, which are cationic species that easily swell in water, because it is assumed that the smectite also functions as a supporting electrolyte for the electrochemical reaction that causes the chemical conversion treatment by completely swelling in water, which is the solvent of the chemical conversion solution. In addition, the cation exchange capacity (CEC) of the smectite is preferably 20 meq / 100 g or more, more preferably 25 meq / 100 g, and most preferably 30 meq / 100 g, from the viewpoint of easy water swelling. In addition, the particle size of the smectite is not particularly limited and can be used.
[0016] The estimated mechanism by which the capacitance is improved by having smectite coexist in the chemical conversion solution is as follows. The surface of the smectite layer, which has a strong interaction with metal ions and metal compounds, strongly interacts with the surface of the aluminum metal layer, and is incorporated into the chemical conversion film during the chemical conversion treatment in a planar oriented state. At this time, the negatively charged smectite layer acts to incorporate metal cations that are not normally incorporated into the chemical conversion film by anodization, promoting polarization in the oxide film and improving the capacitance.
[0017] (water) The chemical conversion solution of the present invention contains water as an essential component. There is no particular limitation on the water used, but from the viewpoint that it is better that the oxide film produced during the chemical conversion treatment does not contain components other than smectite, it is preferable to use water from which ionic components have been removed, such as distilled water or ion-exchanged water. The degree of ion removal is preferably such that the ionic conductivity of the water is 10 μS / m or less, more preferably 5 μS / m or less, and even more preferably 1 μS / m or less.
[0018] (pH of chemical solution) There is no particular restriction on the pH of the chemical conversion solution used in the present invention. When only smectite in which the interlayer metal is sodium or lithium is dispersed in water, the pH is generally in the weak alkaline range of about 10 to 11. The chemical conversion solution may be used as is, or the pH may be adjusted to a neutral to acidic range by adding an acid component, or the pH may be adjusted to a highly alkaline range by adding an alkaline component. However, it is preferable that the pH be in a range in which the smectite can maintain a swollen state in water.
[0019] (Concentration of smectite in chemical solution) There is no particular limitation on the concentration of the smectite component in the chemical conversion solution used in the present invention. From the viewpoint of obtaining the effect of the chemical conversion treatment and maintaining the fluidity of the chemical body to facilitate the chemical conversion treatment, the content of smectite in the chemical conversion solution is preferably 0.1 to 20 mass%, more preferably 0.5 to 15 mass%, and most preferably 1 to 10 mass%.
[0020] <Other ingredients> The chemical conversion solution of the present invention may contain other components within a range that does not impair the effects of the present invention. For example, in order to facilitate the progress of the chemical conversion treatment, it may contain ammonium borate or ammonium adipate, which is a supporting electrolyte of an electrolyte used in a known aluminum chemical conversion treatment. It may also contain other salts that function as supporting electrolytes. As other additives, it may contain stabilizers, defoamers, pH adjusters, specific gravity adjusters, viscosity adjusters, wettability improvers, chelating agents, oxidizing agents, reducing agents, organic solvents, surfactants, etc. The other additives may be used alone or in combination of two or more. The content of the additives in the chemical conversion solution is preferably 0.01 to 10 mass% per additive so as not to impede the effect of the smectite on the chemical conversion treatment.
[0021] A method for chemically treating an aluminum substrate according to one embodiment of the present invention (hereinafter also simply referred to as a "chemical treatment method") includes a step of chemically treating an aluminum substrate by anodization using the above-mentioned chemical conversion solution to obtain a chemically treated substrate having an aluminum oxide film formed on its surface.
[0022] The conditions for anodizing an aluminum substrate using the chemical conversion solution of the present invention are not particularly limited, and normal conditions can be applied. The temperature during anodization is preferably a temperature at which the chemical conversion solution exists stably as a liquid. Specifically, the temperature is preferably 0 to 95°C, more preferably 10 to 95°C, and even more preferably 20 to 90°C. The current and voltage during anodization may be appropriately controlled so as to achieve conditions for forming an oxide film (aluminum oxide film) on the surface of the substrate. Usually, anodization is performed at a constant current until a predetermined chemical conversion voltage (Vf) is reached, and then the chemical conversion voltage (Vf) is maintained for a certain period of time for anodization. The current density is 0.1 to 100 mA / cm 2 It is preferable to set the current within the range of 0.5 to 50 mA / cm 2It is more preferable that the formation voltage (Vf) is within the range of 2 to 800 V, preferably within the range of 5 to 700 V, and more preferably within the range of 8 to 650 V. Anodization may be performed with AC having a constant peak current value until the formation voltage (Vf) is reached, and then switched to DC when the formation voltage (Vf) is reached and maintained for a certain period of time.
[0023] In the chemical conversion treatment method of the present embodiment, the entire substrate may be anodized, or only a portion of the substrate may be anodized. When forming an aluminum oxide film on a portion of the substrate surface, the portion to be anodized may be selected in advance using a method such as photoresist.
[0024] The electrode material for an aluminum electrolytic capacitor according to one embodiment of the present invention includes the above-mentioned chemically treated substrate.
[0025] Furthermore, a capacitor can be manufactured by using the above-mentioned electrode material for aluminum electrolytic capacitors. That is, a capacitor according to one embodiment of the present invention is provided with the above-mentioned electrode material for aluminum electrolytic capacitors. The above-mentioned capacitor provided with the electrode material for aluminum electrolytic capacitors can be manufactured by a known method. The capacitor further includes an electrolytic solution, a separator, electrolytic paper, and the like in addition to the electrode material (anode material and cathode material) of the present invention. EXAMPLES
[0026] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto.
[0027] <Chemical liquid> (Chemical conversion solution used in Examples 1 to 4) As shown in Table 1, various smectites were dispersed in distilled water (electrical conductivity 0.2 μS / cm or less) to obtain 1-5 mass% viscous, nearly transparent liquids. The chemical conversion solutions of Examples 1, 2, and 4 exhibited an alkaline pH of 10-11. In Example 3, 11 g of 0.2 M sulfuric acid solution was added dropwise to 100 g of a 2 mass% Stevensite aqueous solution while stirring with a stirrer, to obtain a chemical conversion solution in which the clay dispersion was adjusted to pH 7.
[0028] (Conversion solution used in Comparative Examples 1 and 2) As shown in the formulation in Table 1, a chemical conversion solution not containing smectite was obtained by dissolving a specified supporting electrolyte in distilled water (electrical conductivity 0.2 μS / cm or less). The pH of the chemical conversion solution obtained for each of the above examples and comparative examples was measured using a pH meter (manufactured by Horiba, Ltd., model number: LAQUAtwin-PH-33B).
[0029] (Aluminum base) The aluminum substrate used for the chemical conversion treatment was a 4N high-purity aluminum foil. 2 A flag-shaped electrode was made by connecting aluminum foil without cutting it to supply power to this electrode, and this was used as the aluminum substrate for chemical conversion treatment. In addition, to clean the electrode surface before carrying out the chemical conversion treatment described below, surface oil and other substances were removed by alkaline degreasing using a 1M aqueous solution of sodium hydroxide. After that, the electrode was washed three times in pure water, neutralized in a 1M aqueous solution of nitric acid, and then washed again three times in pure water, and the following chemical conversion treatment was carried out immediately.
[0030] (chemical treatment) A stainless steel container (Sus304) with an inner diameter of 30 mm was filled with the chemical conversion solution prepared for each Example and Comparative Example, and only the electrode portion of the aluminum substrate was immersed in the solution. The aluminum substrate and the stainless steel container corresponding to the counter electrode were connected to a high-voltage power supply for chemical conversion treatment (Takasago Manufacturing Co., Ltd., HV-1.5-03) and a digital multi-tester for measuring current and voltage (Sanwa Electric Instruments Manufacturing Co., Ltd., model number: RD701), and the solution was heated at 25°C and had a current density of 1 mA / cm. 2The chemical conversion treatment was carried out under the above conditions until the voltage reached 10 V.
[0031] (Evaluation of electrostatic capacitance of chemical conversion film) The electrostatic capacitance of aluminum substrates having oxide films formed by the above-mentioned chemical conversion treatments using the chemical conversion solution compositions of each Example and Comparative Example was evaluated. Using a 15 mass% aqueous solution of ammonium adipate previously prepared as an electrolyte, 1 cm of each chemical conversion film was measured using an LCR meter (manufactured by NF Corporation, model number: ZM2355) based on the electrostatic capacitance test method for low-voltage chemical conversion foils under conditions of a frequency of 120 Hz, a measurement voltage of 0.5 Vrms, and a bias voltage of 1.5 V. 2 The capacitance C per unit was measured. The measurement results are shown in the capacitor evaluation column at the bottom of Table 1.
[0032] (Evaluation of the dielectric strength of chemical conversion films) The chemical conversion films obtained using the chemical conversion solutions and devices used in the Examples and Comparative Examples were subjected to re-chemical conversion treatment under the same operation and conditions. The voltage value immediately after the start of the re-chemical conversion treatment in this treatment process was taken as the film withstand voltage / V and was used as an index of the withstand voltage of the capacitor.
[0033] (Evaluation of the capacity of chemical conversion film) The CV product was calculated from the capacitor evaluation results for the composition of the chemical conversion solution used in each Example and Comparative Example. The CV product was calculated by multiplying the above (evaluation result of the electrostatic capacitance of the chemical conversion film) by (evaluation result of the film withstand voltage of the chemical conversion film). This value was used as an index of the capacitor's charge storage capacity.
[0034] [Table 1]
[0035] Chemical conversion solution used (Smectites) Mineral name: Hectorite; Product name: Sumecton-SWN; Cation exchange capacity: 43 meq / 100 g Mineral name: Saponite; Product name: Sumecton-SA; Cation exchange capacity: 66 meq / 100 g Mineral name: Stevensite; Product name: Sumecton-ST; Cation exchange capacity: 25 meq / 100 g In both cases, the correlated ion is sodium ion, manufactured by Kunimine Kogyo Co., Ltd. (others) Ammonium adipate, sodium hydroxide, sodium bicarbonate, nitric acid 1.38: all Fujifilm Wako Pure Chemical reagents, special grade.
[0036] As shown in the lower part of Table 1, the electrolytic capacitors (Examples 1 to 4) having an aluminum oxide film obtained by performing a chemical conversion treatment by anodization in a dispersion liquid composed of smectite and water, which is the chemical conversion liquid of the present invention, showed the same film withstand voltage value as the capacitors made from the two types of electrolytes not containing smectite in Comparative Examples 1 and 2. In addition, the aluminum electrolytic capacitors obtained in Examples 1 to 4 showed a 25 to 50% increase in capacitance compared to the capacitors in Comparative Examples 1 and 2, and were able to be capacitors with high capacitance.
Claims
1. at least, (A) Smectite (B) Water Contains A chemical conversion solution for anodizing an aluminum substrate, having a pH of 7 to 11.
2. The chemical conversion solution according to claim 1 , wherein the smectite is a synthetic smectite.
3. The chemical conversion solution according to claim 1 or 2, wherein the content of smectite in the chemical conversion solution is 0.1 to 20 mass %.
4. A method for chemically treating an aluminum substrate, comprising the steps of: anodizing an aluminum substrate in a chemical solution for anodizing an aluminum substrate, the chemical solution containing at least smectite and water, to obtain a chemically treated aluminum substrate having an aluminum oxide film formed on its surface.
5. A method for producing a chemically treated aluminum substrate, comprising the steps of: chemically treating an aluminum substrate by anodizing in a chemical solution for anodizing an aluminum substrate, the chemical solution containing at least smectite and water, to obtain a chemically treated aluminum substrate having an aluminum oxide film formed on its surface.
6. A method for producing a capacitor, comprising the step of incorporating an electrode material for an aluminum electrolytic capacitor, the electrode material including a chemically treated aluminum base material obtained by the method for producing a chemically treated aluminum base material according to claim 5, into a capacitor.
Citation Information
Patent Citations
Metal surface pretreatment and composition therefor
JP1984226181A
Phosphate chemical treatment method
JP1993306497A
Manufacture of electrode foil for aluminum electrolytic capacitor
JP2000348984A
Surface treatment agent having excellent cathode peeling resistance, and double corrosion protective-covered steel using the same
JP2004238680A
Aqueous lubricating coating agent for metal material, surface treatment metal material and method for forming lubricating coating of metal material
JP2016204724A